Indications, complications and outcomes of minimally-invasive lateral lumbar interbody fusion with anterior column realignment vs. standard LLIF using expandable interbody spacers - Fischer, Gregor; Bättig, Linda; Schöfl, Thomas; Schonfeld, Ethan; Veeravagu, Anand; Martens, Benjamin; Stienen, Martin N. (Frontiers in Surgery, 2024)
BackgroundAnterior column realignment (ACR), using a lateral lumbar or thoracic interbody fusion (LLIF) approach to release the anterior longitudinal ligament (ALL), is a powerful technique to increase segmental lordosis. We here report our experience with the use of expandible LLIF cages for ACR.MethodsRetrospective, single-center observational cohort study including consecutive patients treated by LLIF using an expandible interbody implant. Patients with ACR were compared to patients without ACR. Our outcomes include adverse events (AEs), radiological (segmental sagittal cobb angle, spinopelvic parameters) and clinical outcomes until 12 months postoperative.ResultsWe identified 503 patients, in which we performed LLIF at 732 levels. In 63 patients (12.5%) and 70 levels (9.6%) an expandable cage was used. Of those, in 30 patients (47.6%) and 30 levels, the ALL was released (42.8%). Age (mean 61.4 years), sex (57.1% female), comorbidities and further demographic features were similar, but patients in the ACR group had a higher anesthesiologic risk, were more frequently operated for degenerative deformity and had a more severely dysbalanced spine (all p < 0.05). ACR was most frequently done at L3/4 (36.7%) and L4/5 (23.3%), entailing multilevel fusions in 50% (3–7 levels) and long constructs in 26.7% (>7 levels). Intraoperative AEs occurred in 3.3% (ACR) and 3.0% (no ACR; p = 0.945). In ACR cases, mean segmental lordosis changed from −2.8° (preoperative) to 16.4° (discharge; p < 0.001), 15.0° (3 months; p < 0.001) and 16.9° (12 months; p < 0.001), whereas this change was less in non-ACR cases [4.3° vs. 10.5° (discharge; p < 0.05), 10.9 (3 months; p < 0.05) and 10.4 (12 months; p > 0.05)]. Total lumbar lordosis increased from 27.8° to 45.2° (discharge; p < 0.001), 45.8° (3 months; p < 0.001) and 41.9° (12 months; p < 0.001) in ACR cases and from 37.4° to 46.7° (discharge; p < 0.01), 44.6° (3 months; n.s.) and 44.9° (12 months; n.s.) in non-ACR cases. Rates of AEs and clinical outcomes at 3 and 12 months were similar (all p > 0.05) and no pseudarthrosis at the LLIF level was noted.ConclusionsACR using an expandible LLIF interbody implant was safe, promoted solid fusion and restored significantly more segmental lordosis compared to LLIF without ALL release, which was maintained during follow-up.